PERBANDINGAN FUNGSI KOGNITIF PADA AKSEPTOR PIL KB KOMBINASI DENGAN AKSEPTOR SUNTIK KB 1 BULAN DI WILAYAH KERJA PUSKESMAS PASAYANGAN - Yasmin, Alfi; Noor, Meitria Syahadatina; Mahmudah, Riva’atul (FKM - UNEJ, 2010)
Family Planning National Program is a program designed by government with the aim to control birthrate, one of which is the hormonal method, that contained estrogen and progesterone hormones. Aside from its sexualÂ and reproductive functions, estrogen can be used to prevent the degradation of cognitive function. The purpose of this research was to find out the comparison of cognitive function of oral contraceptive usersÂ and the monthly injected contraceptive users by using Mini Mental State Examination (MMSE) test in the area Pasayangan Public Health Center Kabupaten Banjar. It was an analytic observational study, with cross sectional design, and the subjects were 30 oral users and 30 monthly injected contraceptive users in the area Pasayangan Public Health Center Kabupaten Banjar. The result of this study indicated that there were 18 monthly injected contraceptive users who had good cognitive function, bigger in number than the oral contraceptive users (13 subjects). Analysis with Mann-Whitney test gave p value ofÂ 0.026 (p < 0.05), which showed that there was a significant difference between oral contraceptive users and monthly injected contraceptive users. It could be concluded that the cognitive function of monthly injected contraceptive users were significantly higher than oral contraceptive users. Keywords: oral contraceptives, injected contraceptives, estrogen, cognitive function